FILSAFAT DAN SEJARAH PERKEMBANGAN ILMU - Muhajirin Muhajirin; Ahmad Syukri; Asrulla (LPPM Universitas Cipta Mandiri, 2024)
Starting from the anxiety that exists within every human being, where we are always confronted with problems that are discussed by terrible thinkers/increasingly calling govesum. The ink strokes only create a surface of unanswered persuasion. This triggers the development of human thought patterns, a sense of curiosity that is learned during this time, of course, choosing a hidden background. The development of knowledge in the present era is one of the subjects that are widely discussed today. Philosophy of science is a continuation of the development of philosophical thought. The object and philosophy of science is the science of knowledge. Therefore, every field of knowledge must follow the development of time and circumstances without neglecting philosophical thinking. That old knowledge will become a guide to find new knowledge. Philosophy is a science that studies the nature of truth in a profound way. Science is a method of thinking objectively in describing and giving meaning to the physical world and has the principle of organizing and systematizing. Indidiction illnu yard. It is cumulative, progressive, and objective. There are six phases of the development of science, including: Pre-Greek Phase, Greek Phase, Medieval Phase, Renaissance Phase, Modern Phase, and the last phase, Contemporary Phase.